FEATURES OF SPEECH THERAPY WORK ON ELIMINATION OF SPEECH DISORDERS IN PRESCHOOLERS WITH LEXICAL AND GRAMMATICAL UNDERDEVELOPMENT OF SPEECH - Коломоєць, Таміла; Прозапас, Жанна (SWorldJournal, 2023)
діти дошкільного віку, мовленнєве порушення, лексико-граматичне недорозвинення мовлення, корекція